2018
DOI: 10.3390/polym10080845
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Hygro-Mechanical Finite Element Method on Determination of the Interlaminar Shear Modulus of Glass Fiber-Reinforced Polymer Laminates in Bridge Decks under Hygrothermal Aging Effects

Abstract: To investigate the mechanical degradation of the shear properties of glass fiber-reinforced polymer (GFRP) laminates in bridge decks under hygrothermal aging effects, short-beam shear tests were performed following the ASTM test standard (ASTM D790-10A). Based on the coupled hygro-mechanical finite element (FE) analysis method, an inverse parameter identification approach based on short-beam shear tests was developed and then employed to determine the environment-dependent interlaminar shear modulus of GFRP la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The introduction of higher-volume and lower-cost fibers, linked with accretions in productivity, has decreased the manufacturing costs of GFRP and CFRP composites. Considering that cost is an important factor influencing demand, maintained advancements in production, along with enhanced availability, are required to promote rising consumption in all areas and applications [192][193][194][195][196][197].…”
Section: Applications Of Gfrp and Cfrp Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of higher-volume and lower-cost fibers, linked with accretions in productivity, has decreased the manufacturing costs of GFRP and CFRP composites. Considering that cost is an important factor influencing demand, maintained advancements in production, along with enhanced availability, are required to promote rising consumption in all areas and applications [192][193][194][195][196][197].…”
Section: Applications Of Gfrp and Cfrp Compositesmentioning
confidence: 99%
“…The introduction of higher-volume and lower-cost fibers, linked with accretions in productivity, has decreased the manufacturing costs of GFRP and CFRP composites. Considering that cost is an important factor influencing demand, maintained advancements in production, along with enhanced availability, are required to promote rising consumption in all areas and applications [192][193][194][195][196][197]. In the United States, CF composites used will likely develop in mass-produced automobiles, contributing lower weight, extra fuel efficiency and more economical emissions; however, more expensive costs will proceed to limit popular use [200].…”
Section: Applications Of Gfrp and Cfrp Compositesmentioning
confidence: 99%
“…In addition, for reducing the weight and enhancing the hardness and strength of the automobile parts, an eco-friendly polymer composite can be used [ 85 , 86 ]. In this case, the epoxy resin represents the matrix of the composite, and the glass and palm fibers strengthened reinforcement [ 87 ]. It has been reported that by increasing the phase ratio of the fiber particles, the tensile strength of the composite is significantly improved [ 88 ].…”
Section: Types Of Synthetic Fibersmentioning
confidence: 99%
“…Pultruded glass fibre reinforced polymer (GFRP) sections have shown potential application for bridges [ 1 , 2 , 3 , 4 ], building construction [ 5 ], and strengthening [ 6 , 7 , 8 ] due to the lightweight, high strength, and corrosion resistance characteristics. Pultruded GFRP is an orthotropic material with mostly unidirectional fibres aligned along the pultrusion direction.…”
Section: Introductionmentioning
confidence: 99%